(3GdSja GdeSfhf GddeGY Ydi GdeaJhf HGdGHJOGYs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s ((3HLhGQ GdeOQSI GdHGPQGJjI ai eOjfI OeTb s)
(3ChdgG (B:s
(3hHYO abO hbYJ MGOKI aCfcQgG s
(3BNQgG (B:s
(3hSjYde GdPjf XdehG Ci efbdH jfbdHhf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
Keywords: (3CUhd Gdabgs